2020
DOI: 10.1177/2056305120915618
|View full text |Cite
|
Sign up to set email alerts
|

Cybervetting and the Public Life of Social Media Data

Abstract: The article examines whether and how the ever-evolving practice of using social media to screen job applicants may undermine people’s trust in the organizations that are engaging in this practice. Using a survey of 429 participants, we assess whether their comfort level with cybervetting can be explained by the factors outlined by Petronio’s communication privacy management theory: culture, gender, motivation, and risk-benefit ratio. We find that respondents from India are significantly more comfortable with s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 66 publications
(98 reference statements)
1
22
0
1
Order By: Relevance
“…The first stage is the collection of data on youtube platforms related to the channels and content of the agricultural sector and conducting live interviews with youth. This practice aims to provide the best information [17].…”
Section: Process Research Methods and Research Designmentioning
confidence: 99%
“…The first stage is the collection of data on youtube platforms related to the channels and content of the agricultural sector and conducting live interviews with youth. This practice aims to provide the best information [17].…”
Section: Process Research Methods and Research Designmentioning
confidence: 99%
“…As individuals post personal information on their online profile pages, it offers businesses opportunities to scrutinize job applicants more closely. For instance, online information can be used to check the veracity of information that candidates provided on their resume [7,11,12]. It also allows recruiters to get a sense of who the candidates are and to make sense of the narrative that job seekers use to tell their story [11].…”
Section: Literature Review 21 the Challenges Of E-recruitment And Cyb...mentioning
confidence: 99%
“…Job applicants' attitudes towards cybervetting may be culturally specific, as differences were found between India and the United States. However, there is no difference in attitudes towards the practice of cybervetting based on gender or the current employment status [7].…”
Section: Introductionmentioning
confidence: 95%
“…A survey from previous work showed that the social media job screening performed by corporations in the United States for job candidates has risen to 70% in 2018 after it was around 11% in 2006 [10]. The companies tend authenticate applicants' skills, evaluate if they introduce themselves in a professional way, and guarantee that these applicants do not have any posts that can be categorized as bullying or insulting content [10]. Thus, when employers or hiring managers have the chance to reach such "reliable data", it can be referred to as cybervetting [4].…”
Section: Approaches To Restrict Social Media Data Misusementioning
confidence: 99%